5.1: Invited Paper: Digital Optics Education, Research & Development, Technology Infrastructure. (24th February 2021) - Tsai, Chun-Wei; Shieh, Chen-Yu; Lin, T. I.; Tai, Ken
Abstract : Digital Optics based on digital electro optics platform is the main concept of Jasper Display Corp. (JDC) to develop various applications. These applications are based on our X on CMOS technologies, for example, Liquid Crystal on CMOS is called LCoS. JDC support LCoS Spatial Light Modulator (SLM) for education kit (EDK), amplitude modulation kit (ARK) and phase modulation kit (SRK) for research. All are plug‐play. SLM in Optics is similar to FPGA in electronics. JDC's digital modulation software is the solution for pixel micro LED platform. Software is the Key to maximize the value for pixel micro LED platform.